Effects of Chemical Compounds upon Current Induced Thrombosis in Rat Mesenteric Vessels - Aaron, R. K; Srinivasan, S; Burrowbs, B; Sawyer, P. N (Thrombosis and Haemostasis, 1970)
From previous work in our laboratories, there is a large amount of evidence for an electrochemical mechanism of thrombosis. The blood vessel wall and blood cells are negatively charged under normal conditions. Antithrombogenic drugs increase their negative charge densities while thrombogenic drugs have the opposite effect. Injury makes the blood vessel wall less negatively charged or even positively charged. There is a relation between vascular injury currents and thrombosis. In the present study, the effect of certain chemical agents upon in situ thrombosis in rat mesoappendix vessels, produced by an applied electric current of the sign and magnitude of physiological injury currents, is examined. Compounds such as polyquarternary, with basic groups enhance thrombosis while compounds such as heparin with acidic groups inhibit thrombosis.